Proceedings of the Sixth ACM Symposium on Cloud Computing 2015
DOI: 10.1145/2806777.2806848
|View full text |Cite
|
Sign up to set email alerts
|

Energy proportionality and workload consolidation for latency-critical applications

Abstract: Energy proportionality and workload consolidation are important objectives towards increasing efficiency in largescale datacenters. Our work focuses on achieving these goals in the presence of applications with µs-scale tail latency requirements. Such applications represent a growing subset of datacenter workloads and are typically deployed on dedicated servers, which is the simplest way to ensure low tail latency across all loads. Unfortunately, it also leads to low energy efficiency and low resource utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Previous studies [6,19,56,57] have shown that data centers like Google and Facebook operate at peak load only for a small fraction of the day, where the power consumption and load are proportional. The number of queries per second during a web search, a typical load at Google data center, varies between about 5% and 80% of maximum capacity [31,40,47].…”
Section: Motivationmentioning
confidence: 99%
“…Previous studies [6,19,56,57] have shown that data centers like Google and Facebook operate at peak load only for a small fraction of the day, where the power consumption and load are proportional. The number of queries per second during a web search, a typical load at Google data center, varies between about 5% and 80% of maximum capacity [31,40,47].…”
Section: Motivationmentioning
confidence: 99%
“…In this way is achieved the reduction of the power consumption. Usually, the workload placement problem is modeled as a multi-dimensional bin-packaging problem, as expressed in [45], [42], [29]. Moreover, meta-heuristics such as Ant Colony Optimization [14], [15], [17], Genetic Algorithms [25], [46], [44], [24] are used for power consumption optimization.…”
Section: Analysis Of Power Consumption In Heterogeneous Virtual Machimentioning
confidence: 99%
“…Energy proportional computing: Energy proportional computing have been a major area of research [1], [5], [6], [9], [15], [18], [35]- [37]. In addition, measurements, metrics and trends of energy proportionality have all been well studied [19], [21], [22], [35], [38].…”
Section: Related Workmentioning
confidence: 99%
“…In addition, measurements, metrics and trends of energy proportionality have all been well studied [19], [21], [22], [35], [38]. Energy proportionality techniques has been proposed at the cluster level through workload consolidation and dynamic capacity management with the goal of "right-sizing" the amount of servers in the data center [10], [14]- [16], [36], [37], [39]. These migrationbased techniques are best suited for coarse-grain workload fluctuations in the order of minutes -hours, and typically assumes a stable power budget.…”
Section: Related Workmentioning
confidence: 99%